Zygomatic implants under local anesthesia: A technical note - Nicolas Mathilde; Guiol Julien (EDP Sciences, 2023)
The placement of zygomatic implants is a surgical procedure that is most often performed under general anesthesia, due to the duration and the difficulty of the procedure, and in particular due to the necessity of a significant detachment. However, depending on the operator's experience, this procedure can be performed under local anesthesia. Indeed, this variation offers many advantages. It simplifies the procedure, allows the patient's collaboration as well as a radiological control during the operation and reduces the postoperative effects. It also eliminates any risk related to general anesthesia. It is systematically practiced in our activity with a very good acceptance from the patients.